RANCANG BANGUN SISTEM INFORMASI MANAJEMEN ORGANISASI KEMAHASISWAAN : (STUDI KASUS UNIVERSITAS MADURA) - Ramadhani, Nilam; Syahroni, Abd. Wahab; Wahyudi, Rian (Universitas Islam Balitar, 2022)
College Student Organization is a forum and means to hone students' abilities, self-development and creativity through various campus activities that are oriented towards increasing achievement. College student activities are created and organized by them through College Student Organizations and student activity units. The implementation of college student organization activities at Madura University has several obstacles. These obstacles generally occur because the service process is still manual and has not been recorded digitally. This makes it difficult for student coaches to find data on student organization activities and student activity units. With this information system, management data, activity proposals, accountability reports, student funds and documentation of activities organized by student organizations will be recorded digitally. The results of the User Acceptance Test on 40 student organization administrators presented the percentage of responses related to user satisfaction was 73.25% based on the score interpretation criteria on the Likert scale. This presented that the response related to user satisfaction with the system built is strong and according to needs. This information system is also equipped with security features to protect important data from unauthorized users